2004
DOI: 10.1295/polymj.36.804
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Properties of Different Degree of Branching Polyamides Derived from an ABB′ Type Monomer, 4-(2,4-Diaminophenoxy) Benzoic Acid

Abstract: ABSTRACT:Hyperbranched polyamides with different degree of branchings (DBs) were prepared by different polycondensation conditions from an ABB 0 type monomer, 4-(2,4-diaminophenoxy)benzoic acid. Polyamide (PA1) with multi-amino groups prepared in the presence of (2,3-dihydro-2-thioxo-3-benzoxazolyl) phosphonic acid diphenyl ester (DBOP) and triethylamine as condensing agents at room temperature had lower DB of 0.1. Polyamide (PA2) with multi-amino groups prepared in the presence of triphenylphosphite and pyrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…16 Synthesis of Branched Polyamides with Low Degree of Branching: Method A with DBOP (2a). To a solution of 1 (2.928 g, 0.013 mol) in the 60 mL of NMP, DBOP (5.140 g, 0.0134 mol) and TEA (1.83 mL) were added.…”
Section: Monomer Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…16 Synthesis of Branched Polyamides with Low Degree of Branching: Method A with DBOP (2a). To a solution of 1 (2.928 g, 0.013 mol) in the 60 mL of NMP, DBOP (5.140 g, 0.0134 mol) and TEA (1.83 mL) were added.…”
Section: Monomer Synthesismentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15] We recently reported that the branched polyamides with low degree of branching (low DB) approximately 0.2 prepared by the polycondensation of a ABB 0 type monomer, 4-(2,4-diaminophenoxy) benzoic acid. 16 The polycondensation of ABB 0 type monomer, in which A is a carboxyl group and B and B 0 are amino groups with different circumstance, provides the polyamides with relatively lower degree of branching. The advantage of the branched polyamides with low degree of branching is not only good solubility for aprotic polar solvents such as dimethylformamide (DMF), N,N-dimethyl acetamide (DMAc) and 1-methyl-2-pyroridone (NMP), but also high tensile strength of the casting films.…”
mentioning
confidence: 99%
“…Recently, we prepared hyperbranched polymers, such as aromatic polyamides, [5][6][7][8][9][10][11][12][13][14][15][16][17][18] polyimides, [19][20][21][22][23][24]15,25 polyesters, 26 polysiloxanes, 27,28 poly(benzoxazole)s, [29][30][31][32][33] poly(triphenylamine), 34 PES [35][36][37][38][39] and poly (siloxysilane), [40][41][42][43][44][45] from AB 2 type monomers, and investigated their mechanical properties. Moreover, to synthesize polyamides, 46 polyimides 47,23,48 and polyphthalocyanines, [49][50][51]…”
Section: Introductionmentioning
confidence: 99%
“…Dendritic polymers have received considerable attention due to their unique chemical and physical properties [1][2][3][4][5][6][7]. Hyperbranched polymers show similar properties to those dendrimers, such as low viscosity, high solubility in organic solvents, and lack of significant entanglement in the solid state.…”
Section: Introductionmentioning
confidence: 99%
“…This is advantageous over the multi-step synthesis of dendrimers because of the rapid production in large quantities. It is also well known that the properties of the dendritic polymers depend on terminal functional groups in addition to backbone structure [1][2][3][4][5][6][7]. Therefore, the properties of dendritic polymers can be tuned to some extent by the chemical modification of end functional groups [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%